Import Substitution Policy in the Chemical Industry of Pavlodar Region in the Republic of Kazakhstan - KAZIZOVA, Gulnar Serikbolatovna; KADYROVA, Akmaral Satbekovna; KASHUK, Lyudmila Ivanovna; KAIDAROVA, Lyazzat Kairkenovna; ARYNOVA, Zulfiya Amangeldinovna; UTEBAYEVA, Altyngul Bolatovna; ZOLOTAREVA, Svetlana Vitalyevna (Journal of Advanced Research in Law and Economics; Vol 8 No 1 (2017): JARLE Volume VIII Issue 1 (23) Spring 2017, 2017)
The present paper studies the development of the modern state of the entire industry in the Republic of Kazakhstan using the example of Pavlodar region. The emphasis is placed on the analysis of the main positions on the development of the chemical, oil-refining and petrochemical industries of Pavlodar region in recent years. The article considers investments in the development of the above-mentioned industries in the region. It also provides a brief description of the major industrial companies that sell their products in the studied sectors of the manufacturing industry in the region. The method of the comparative analysis of statistical data on chemical and oil-refining production contributed to studying the quantitative values of these sectors in the context of the region. As a result, the authors propose pursuing the policy of import substitution in the chemical and petrochemical industries in the region as a protectionist policy and realizing the potential for the use of production facilities of the manufacturing industry in Pavlodar region.